Analisis Kemampuan Berpikir Kritis Peserta Didik pada Pembelajaran Sejarah berbasis Materi Sejarah Lokal Kelas XI IPS SMA Negeri 3 Kota Pontianak - Manja, Manja; Zakso, Amrazi; Chalimi, Ika Rahmatika (Jurnal Simki Pedagogia, 2024)
The purpose of this study is to explain the process of delivering historical material using local historical material and to determine the characteristics of students with critical thinking skills and to describe the factors that influence their critical thinking in learning history based on local historical material. The research method used is qualitative. The place of implementation of this research is at SMA Negeri 3 Pontianak. Data collection techniques through interviews and direct observation. Data sources obtained from history teachers, homeroom teachers, and class XI IPS students of SMA Negeri 3 Pontianak City. The results of this study are that class XI IPS students of SMA Negeri 3 Pontianak City have a critical thinking ability profile that includes the ability to describe problems or opinions of others, good communication skills, the ability to find the truth through information research, the ability to accommodate and listen to arguments from others, expertise in solving and providing solutions to existing problems, great curiosity, critical of new information, and fondness for asking and being able to answer questions. The application of critical thinking in local history learning has gone well, marked by student enthusiasm, moral support given by teachers, and the use of interactive learning methods such as brainstorming and discussion activities.